Factors Affecting Hemoglobin Levels in Prospective Female Donors in Semarang Blood Centre (Public Health Perspective Journal, 2022)
The high failure rate to donate blood is one of the main causes of unfulfilled blood needs. One of the causes of blood donation failure is low hemoglobin levels. As for the factors that can affect hemoglobin levels, including age, diet, menstrual patterns, menstrual duration, and so on, the purpose of this study was to determine the factors associated with hemoglobin levels in prospective female donors at the blood center, Indonesian Red Cross (IRC), Semarang City. This research is an analytical survey with a cross-sectional approach. The population of this research is women who had hemoglobin examinations before donating blood at the blood center IRC Semarang City in January–June 2021, totaling 4,661 donors. The sample used is 100, with a sampling technique of simple random. The data analysis techniques used in this study were univariate analysis (frequency distribution), bivariate analysis (chi-square test), and multivariate analysis (multiple logistic regression test). The results showed that there was a significant effect between age, diet, menstrual pattern, duration of menstruation, and smoking history on hemoglobin levels in prospective female donors at the blood center IRC Semarang City with a p-value 0.05. With a p-value greater than 0.05, blood type, occupation, type of donor, duration of donor, education level, and income have no effect on hemoglobin levels in prospective female donors at the IRC Semarang City blood center.